CURRENT SCHOOL CURRICULUM ISSUES: A CASE OF STUDENT-TEACHER PREPARATION IN HIGHER EDUCATION - Christina Kristiyani (Sanata Dharma University Yogyakarta, 2019)
The current curriculum change in Indonesia school has direct impact on the schools, students, teachers, as well as the student teachers. This paper analyses the problems found in the student teachers’ preparation in planning the learning activities in a form of teaching documents. Therefore, the data being analyzed are teaching preparation documents produced by the student teachers before they went for the internship program in schools. The data were from the class documents in the Learning Program Design class and Micro Teaching class during February 2015 – June 2016. The analysis found that the problems are related to the translation from the basic competence into the indicator of achievement and the assessment planning. In addition, they also had difficulties in planning the teaching scenario using the scientific approach. Some solutions are proposed in this paper.